Gender Relations and Conjugality among the Baule (Ivory Coast) - Étienne, Mona (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1981)
Reluctance to marry, urban migration and the pursuit of wealth on the part of contemporary Baule women are here examined in the light of historical and structural factors that play a decisive role in determining present goals and influencing behavior. Politically, economically and socially, women enjoyed high status in precolonial Baule society. Virilocal marriage restricted a woman’s access to political office, but did not prevent her from establishing a personal constituency of dependents and participating in the entrepreneurial activities through which one achieved prosperity and prestige. These opportunities were, however, contingent on a definition of conjugal rights and obligations which gave women, as well as men, control over basic resources. Colonization, by transforming productive relations, has broken down the equilibrium of the conjugal relationship and undermined the economic position of women in general and wives in particular. Yet, it has not destroyed the models and values which motivate many Baule women to pursue economic and personal autonomy, and which sometimes influence men to respect and support these goals.